Pengaruh Needs For Achievement Dan Karakteristik Pribadi Terhadap Keinginan Berwirausaha: Stud i Pada Mahasiswa FE Untar - Fanny Andriani Setiawan (Jurnal Manajemen, 2014)
The purpose of this study was to analyze Effect Needs for Achievement and Personal Characteristics  Of Desire Entrepreneurship: Studies  in  FE Student UNTAR. The  data used  in this  study is primary data obtained  from a questionnaire research instruments were given to FE students UNTAR. Of the 500  questionnaires distributed, the number of questionnaires  returned and deserves to dioleha  of 420 questionnaires. Data using multiple regression analysis to answer the hypothesis peneilitian with the software  PASW  Statistics  18  and  Eviews  6. This  research  was  carried  Faculty of Economics, University  of Tarumanagara,  with the object  of study is  a student.  This study uses survey research with primary data collection using questionnaires. The selection  of samples  tested  in  this  study  using  purposive  sampling  method,  420 respondents was selected as the study sample. The results of this study were (I) Needs for achievement has a positive effect on the willingness of students to entrepreneurship, (2)  Gender positive effect  on the willingness  of students to entrepreneurship, (3) Age does not affect the  desire of students to entrepreneurship,  and (4) work experience possessed FE students UNTAR not affect students for entrepreneurship.